Resistance monitoring and assessment of the control failure likelihood of insecticides in field populations of the whitebacked planthopper Sogatella furcifera (Horváth). (January 2020) - Li, Wenhao; Mao, Kaikai; Liu, Chaoya; Gong, Peipan; Xu, Pengfei; Wu, Gang; Le, Wei; Wan, Hu; You, Hong; Li, Jianhong
Abstract: Sogatella furcifera (Horváth) is a major threat to rice production in China. Insecticides are a key component of typical pest management schemes, but few studies have quantitatively identified insecticide control failures due to insecticide resistance. Therefore, we measured the susceptibility of eight populations to thirteen insecticides by the rice dipping method in 2018 and further evaluated the likelihood of control failure in this study. The results showed that S. furcifera had high levels of S. furcifera resistance to buprofezin (RR = 76.42–160.14-fold), chlorpyrifos (RR = 93.50–219.90-fold), and pymetrozine (RR > 469.30-fold) and low to moderate levels of resistance to nitenpyram (RR = 1.50–10.21-fold), clothianidin (RR = 3.72–20.43-fold), thiamethoxam (RR = 2.88–19.95-fold), imidacloprid (RR = 4.05–31.81-fold), dinotefuran (RR = 4.55–25.98-fold), isoprocarb (RR = 2.55–15.71-fold), and etofenprox (RR = 5.63–17.74-fold). S. furcifera remained susceptible to cycloxaprid (resistance ratio, RR = 0.56–1.82-fold), triflumezopyrim (RR = 0.77–3.23-fold) and sulfoxaflor (RR = 2.28–4.32-fold). Pymetrozine, isoprocarb and etofenprox were determined to be at risk of control failures if the minimum recommended concentration is applied to manage this pest. Furthermore, significant correlations were found among the logarithms of the median lethal concentration (LC50 ) values of thirteen insecticides. Additionally, the activities of esterases in field populations of S. furcifera were significantly positively correlated with the logarithm of the LC50 values of triflumezopyrim, nitenpyram and clothianidin. The results of this survey offer an important basis for producing effective and useful strategies to manage insecticide resistance in S. furcifera . Highlights: High resistance to buprofezin, chlorpyrifos, and pymetrozine in field populations of  S. furcifera  was observed. A risk of control failures of pymetrozine, isoprocarb and etofenprox to manage  S. furcifera was described. Correlations were analyzed between the values of the logarithm of the LC50  values of the insecticides. Significant correlations were found between esterase and the susceptibility to triflumezopyrim, nitenpyram and clothianidin.